Helicobacter pylori exploits the NLRC4 inflammasome to dampen host defenses - Semper, Raphaela P.; Vieth, Michael; Gerhard, Markus; Mejías-Luque, Raquel (Journal of Immunology, 2019)
Helicobacter pylori colonizes the stomach of around 50% of humans. This chronic infection can lead to gastric pathologic conditions such as gastric ulcers and gastric adenocarcinomas. The strong inflammatory response elicited by H. pylori is characterized by the induction of the expression of several cytokines. Among those, IL-18 is found highly upregulated in infected individuals, and its expression correlates with the severity of gastric inflammation. IL-18 is produced as inactive proform and has to be cleaved by the multiprotein complex inflammasome to be active. In immune cells, the NLRC4 inflammasome, which is activated by flagellin or bacterial secretion systems, was shown to be dispensable for H. pylori-induced inflammasome activation. However, apart from immune cells, gastric epithelial cells can also produce IL-18. In this study, we analyzed the role of the NLRC4 inflammasome during H. pylori infection. Our results indicate that NLRC4 and a functional type IV secretion system are crucial for the production of IL-18 from human and murine gastric epithelial cells. In vivo, Nlrc4-/- mice failed to produce gastric IL-18 upon H. pylori infection. Compared with wild type mice, Nlrc4-/- mice controlled H. pylori better without showing strong inflammation. Moreover, H. pylori-induced IL-18 inhibits β-defensin 1 expression in a NF-κB-dependent manner, resulting in higher bacterial colonization. At the same time, inflammasome activation enhances neutrophil infiltration, resulting in inflammation. Thus, NLRC4 inflammasome activation and subsequent IL-18 production favors bacterial persistence by inhibiting antimicrobial peptide production and, at the same time, contributes to gastric inflammation.
CRIS-Team Scopus Importer:2025-03-05